PENERAPAN AKAD MUSYARAKAH TERHADAP BISNIS TOKO KELONTONG - Aldy Yahya Imam Mujahidin Saputra; Jaenudin Jaenudin; Dian Herdiana (CV. Denasya Smart Publisher, 2025)
This study analyzes the implementation of the musyarakah contract in a grocery business in Cimahi using a qualitative juridical-empirical approach. The analysis focuses on the implementation mechanism, legal compliance, supporting and inhibiting factors, and its impact on business development. Interviews with business owners revealed that revenue was initially divided based on work shifts, which did not fully align with the musyarakah profit-sharing principle. However, adjustments to the agreement enabled compliance with Sharia by separating capital-based profit from wage-based compensation (ujrah). Legally, the practice aligns with DSN-MUI Fatwa No. 08/2000, KHES, and Sharia financing regulations as long as capital, profit-sharing ratios, and loss allocation are transparently stated. The partnership’s success is supported by trust, open communication, and business integrity, while challenges arise from low Sharia financial literacy and weak record-keeping. Overall, musyarakah positively influences business growth through increased revenue, better governance, and fairer profit distribution.